EDITORIAL (KEMANUSIAAN The Asian Journal of Humanities, 2018)
The current issue of KEMANUSIAAN the Asian Journal of Humanities comprises six articles in the areas of linguistics, literature, history, geography and translation. The first article is an analysis of a well-known English literary work, i.e., Persuasion by Jane Austen, using a corpus stylistic approach. The article discusses how grammatical forms contribute meaning in literary texts by analysing two statistically significant nouns in the novel. The findings on the singular and plural forms of the words reveal the significant role they have in thematic meaning construction as well as the narrative techniques used in the novel.